Altered galectin-3 distribution and migratory function in the pre-diabetic non-obese diabetic mouse thymus - Ramos, Tiago Dutra Pereira; Ventura, Ana Lucia Marques; Lemos, Julia Pereira; Chammas, Roger; Savino, Wilson; Carvalho-Pinto, Carla Eponina; Mendes-da-Cruz, Daniella Arêas; Villa-Verde, Déa Maria Serra (Frontiers in Endocrinology, 2024)
Galectin-3 is an endogenous lectin which binds mainly to β-galactosides on the cell surface and extracellular matrix (ECM) glycoproteins. In the thymus, this lectin is constitutively expressed, being involved in thymocyte adhesion, migration, and death. Galectin-3 has been related to type 1 diabetes, an autoimmune disease characterized by pancreatic β-cell destruction mediated by autoreactive T lymphocytes. Non-obese diabetic (NOD) mice represent a suitable model to study type 1 diabetes, as they develop the disease like humans. We previously described important thymic alterations in these animals such as the development of giant perivascular spaces (PVS), characterized by the retention of T and B cells, intermingled with an ECM network, and associated with a defect in the expression of the fibronectin receptor VLA-5 and reduced sphingosine-1-phosphate receptor expression on developing thymocytes. In order to investigate galectin-3 expression in thymic microenvironmental cells and verify its interaction with cells and ECM molecules in PVS, we performed immunofluorescence following colocalization analysis in the thymic parenchyma of pre-diabetic NOD mice by confocal microscopy. In addition, thymocyte migration assays were performed to evaluate the effect of galectin-3 on NOD thymocyte migration. Herein, we showed a significant enhancement of colocalization with cortical and medullary thymic epithelial cells in NOD mice, as compared to controls. In the giant PVS of these animals, we observed a heterogeneous distribution of galectin-3, predominantly found in clusters of B lymphocytes and dendritic cells. Functionally, NOD thymocyte migratory response towards galectin-3 was impaired and a similar decrease was seen in transendothelial thymocyte migration. Taken together, our data provide the histological and functional background for a potential defective thymocyte migration involving galectin-3, thus placing this molecule as a further player in the intrathymic disturbances observed in pre-diabetic NOD mice.